A Study on Glass Fibre as an Additive in Concrete to Increase Compressive Strength - Khamkar, Prof. Rajendra S.; Khamkar, Mohini A.; Pathare, Ganesh R. (International Journal of Scientific Research in Civil Engineering, 2020)
Concrete paver blocks were invented in Holland, in the fifties as replacement of paver bricks which had become scarce due to the post-war building construction boom. These blocks were rectangular in shape and had more or less the same size as the bricks. During fifty year, the block shape has steadily evolved from non-interlocking to partially interlocking to fully interlocking shapes. Consequently, the pavements in which no interlocking blocks are used are designated as “Concrete Block Pavement (CBP)” or non-interlocking CBP, and those in which partially, or fully interlocking blocks are used are designated as “Interlocking Concrete Block Pavement.”
Keywords: Conventional Blocks; Compressive Strength; Paver Blocks; coir fibre; Fly Ash